The effect of vitamin D supplementation on increasing CD4 levels in human immunodeficiency virus: evidence-based report - Rachmawati, Dessy Suci; Sunardi, Diana (Indonesian Nutrition Association, 2024)
Introduction: Human immunodeficiency virus (HIV) is a retrovirus infection that attacks the immune system. According to world data in 2016, the number of HIV-infected patients reached 36.7 million, and 10 million people died due to acquired immunodeficiency syndrome (AIDS). Patients with HIV infection are susceptible to decreased levels of vitamin D (25(OH)D) by proinflammatory cytokines or as a result of the use of antiretroviral drugs. Vitamin D plays an important role in immune system, including reducing the production of pro-inflammatory cytokines and increasing the production of cathelicidin that inhibit viral replication. Oral vitamin D supplementation is an effort that can be made to increase vitamin D. To date, the relationship between vitamin D sufficiency and CD4 T cell count remains unclear, although most studies have shown a positive association. This study wanted to determine the effect of oral vitamin D supplementation on increasing CD4 levels in patients with HIV infection. Methods: Literature search was carried out by advanced searching on Pubmed, Cochrane Library, and Science Direct using eligibility criteria determined by the authors. Result: One systematic review and three randomized controlled trials (RCT) met the PICO and eligibility criteria that had been set. Three studies concluded that vitamin D supplementation can increase CD4 levels. One study shows that vitamin D supplementation dose of 5,000 IU daily could not increase CD4 levels. Conclusion: Providing vitamin D supplementation at appropriate dose can increase serum vitamin D levels so that it can increase CD4 levels.